Cultivating Early Childhood Characters Through Animated Films Nussa and Rara - Nurmala, Siti; Rosidah, Laily; Khosiah, Siti (Universitas Lancang Kuning, 2023)
The use of gadgets can have a positive impact on children, but it does not rule out the possibility that gadgets can also have many negative impacts on children's character, such as the impressions given to children. Therefore, assistance and supervision is needed in selecting shows given to children, namely through the animated films Nussa and Rara. The aim of this research is to determine the cultivation of character in early childhood through the animated film Nussa and Rara in Sukaraja village, Cikeusal subdistrict, Serang-Banten regency. The method in this research was Qualitative Descriptive. Therefore, the data were taken using interview, observation, and documentation techniques. Interactive models adapted from Milles and Huberman, including data reduction, data presentation, and drawing conclusions was used as the technique of data analysis. As a conclusion, the results obtained show that the character cultivation in children has been well ingrained in accordance with the indicators that have been determined, including 5 children developing according to expectations, 1 child starting to develop, and 1 child still needs help. Success in instilling character in children can be found when character values ​​are manifested and developed in the child's behavior in everyday life in accordance with the goals of character education.